Influence of different pig genotype on aroma, colour and fatty acid composition of smoked dry-cured ham - Marušić, Nives, inženjerka prehrambene tehnologije; Poljanec, Ivna; Vidinski, Petra; Novina, Katarina; Medić, Helga (2019)
The aim of this study was to determine the influence of different genotypes of pigs ((Landrace x large Yorkshire) x Duroc (LYD) and Black Slavonian (BS) pig) on the colour, fat content and fatty acid composition of smoked dry-cured ham and identify volatile aroma-active compounds. The fat content was determined by applying the Smedes method and the composition of fatty acids by using the gas chromatography, while volatile aroma-active compounds were investigated by using the headspace-solid phase microextraction (HS-SPME) and the gas chromatography-mass spectrometry (GC-MS). Different genotypes of pigs did not show a statistically significant difference (p>0.05) in total fat content, but there was a difference in the proportion of individual fatty acids. We identified a total of 103 volatile compounds belonging to the following groups of chemical compounds: 19 aromatic hydrocarbons, 17 aliphatic hydrocarbons, 17 ketones, 15 phenols, 14 aldehydes, 11 alcohols, 5 acids, 2 terpenes and 1 sulphur compound. The most abundant chemical groups of compounds in samples of smoked dry-cured ham from LYD pigs were aldehydes, phenols and aromatic hydrocarbons, while the most abundant chemical groups of compounds in samples of smoked dry-cured ham of BS genotype were phenols, aldehydes and alcohols.
Cilj ovog rada bio je odrediti utjecaj različite pasmine svinja (tropasminski križanac (landras x veliki jorkšir) x durok (LYD) i crna slavonska (CS) svinja) na boju, udio masti i sastav masnih kiselina u dimljenom pršutu te odrediti hlapive spojeve arome. Udio masti određen je metodom po Smedesu, sastav masnih kiselina određen je metodom plinske kromatografije, dok su hlapivi spojevi arome određeni mikroekstrakcijom na čvrstoj fazi (SPME) i plinsko kromatografsko-masenom spektrometrijom (GC-MS). Iako različita pasmina svinja nije pokazala statistički značajnu razliku (p>0,05) u ukupnom udjelu masti, zabilježena je statistički značajna razlika u udjelima pojedinih masnih kiselina. Identificirano je ukupno 103 hlapiva spoja arome, a pripadaju sljedećim grupama kemijskih spojeva: 19 aromatskih ugljikovodika, 17 alifatskih ugljikovodika, 17 ketona, 15 fenola, 14 aldehida, 11 alkohola, 5 kiselina, 2 terpena, 2 estera i 1 spoj sa sumporom. U uzorcima dimljenog pršuta LYD genotipa, najzastupljenije grupe spojeva bile su: aldehidi, fenoli i aromatski ugljikovodici dok su u uzorcima dimljenog pršuta CS najzastupljenije grupe spojeva bile: fenoli, aldehidi i alkoholi.
Das Ziel dieser Studie war es, die Wirkung von verschiedenen Schweinegenotypen ((Landrasse- x Yorkshire) x Duroc (LYD) und schwarzes slawonisches (CS) Schwein)) auf die Farbe, den Fettanteil und die Fettsäurezusammensetzung von geräucherten Rohschinken zu bestimmten und die flüchtigen Aromainhaltsstoffe zu identifizieren. Der Fettanteil wurde durch die Anwendung der Smedes-Methode bestimmt, die Zusammensetzung der Fettsäuren anhand der Gaschromatographie-Massenspektrometrie, während die flüchtigen Aromainhaltsstoffe unter Verwendung der Headspace-Festphasenmikroextraktion (HSSPME) und der Gaschromatographie mit Massenspektrometrie untersucht wurden (GC-MS). Obwohl unterschiedliche Schweinegenotypen keinen statistisch signifikanten Unterschied (p>0,05) im Gesamtfettanteil gezeigt haben, gab es jedoch einen Unterschied im Anteil der einzelnen Fettsäuren. Es wurden insgesamt 103 flüchtige Aromainhaltsstoffe identifiziert, die den folgenden Gruppen von chemischen Verbindungen zugeordnet werden können: 19 aromatische Kohlenwasserstoffe, 17 aliphatische Kohlenwasserstoffe, 17 Ketone, 15 Phenole, 14 Aldehyde, 11 Alkohole, 5 Säuren, 2 Ester und 1 Schwefelverbindung. Die am häufigsten vorkommenden Gruppen von chemischen Verbindungen im geräucherten Rohschinken von LYD-Schweinen waren Aldehyde, Phenole und aromatische Kohlenwasserstoffe, während die am häufigsten vorkommenden Gruppen von Verbindungen in geräuchertem Rohschinken des Genotyps CS Phenole, Aldehyde und Alkohole waren.
El fin de este trabajo fue determinar el impacto de diferentes razas de cerdos (el híbrido de tres razas (el Landrace x la raza de cerdo yorkshire grande) x el Duroc (LYD) y el Cerdo Negro de Eslavonia (CS)) sobre el color, el contenido de grasas y la composición de los ácidos grasos en el jamón curado ahumado y determinar los compuestos aromáticos volátiles. El contenido de grasas fue determinado por el método Smedes, la composición de los ácidos grasos fue determinada por la cromatografía de gases y los compuestos aromáticos volátiles fueron determinados por la microextracción en fase sólida (SPME) y por la cromatografía de gases-espectrometría de masas, GC-MS. Aunque las razas de cerdos diferentes no mostraron las diferencias estadísticamente significativas (p>0,05) en el contenido total de grasas, fue determinada la diferencia estadísticamente significativa en el contenido de varios ácidos grasos. Fueron identificados 103 compuestos aromáticos volátiles en total, pertenecientes a siguientes grupos de compuestos químicos: 19 hidrocarburos aromáticos, 17 hidrocarburos alifáticos, 17 cetonas, 15 fenoles, 14 aldehídos, 11 alcoholes, 5 ácidos, 2 terpenos, 2 ésteres y 1 compuesto de azufre. En las muestras del jamón ahumado del genotipo LYD, los grupos de compuestos más representados fueron: aldehídos, fenoles e hidrocarburos aromáticos, mientras en las muestras del jamón ahumado CS los compuestos más representados fueron: fenoles, aldehídos y alcoholes.
Questa ricerca ha voluto stabilire l’impatto di diverse razze suine - incrocio di tre razze: landrace x grande bianco o Yorkshire x duroc (LYD) e maiale nero di Slavonia (CS), sul colore, sulla percentuale di grassi e sulla composizione degli acidi grassi nel prosciutto crudo affumicato, oltre ad individuare i composti volatili dell’aroma. La percentuale di grassi è stata stabilita mediante il metodo d’analisi secondo Smedes, la composizione degli acidi grassi è stata accertata mediante la gascromatografia, mentre i composti volatili dell’aroma sono stati accertati mediante la tecnica della microestrazione in fase solida (SPME) e la gascromatografia accoppiata alla spettrometria di massa (GC-MS). Sebbene le differenti razze suine non abbiano mostrato una differenza statisticamente rilevante (p>0,05) riguardo alla percentuale totale di grassi, è stata registrata, invece, una differenza statisticamente rilevante riguardo alle percentuali di singoli acidi grassi. Circa i composti volatili dell’aroma, ne sono stati identificati 103 in totale, appartenenti ai seguenti gruppi di composti chimici: 19 idrocarburi aromatici, 17 idrocarburi alifatici, 17 chetoni, 15 fenoli, 14 aldeidi, 11 alcoli, 5 acidi, 2 terpeni, 2 esteri e 1 composto con lo zolfo. Nei campioni di prosciutto crudo affumicato del genotipo LYD è stata accertata una maggior presenza dei seguenti gruppi di composti: aldeidi, fenoli e idrocarburi aromatici. Nei campioni di prosciutto crudo affumicato del genotipo CS, invece, è stata accertata una maggior presenza dei seguenti gruppi di composti: fenoli, aldeidi e alcoli.
Bibliografija: 39 jed.
Abstract ; Sažetak ; Zusammenfassung ; Resumen ; Riassunto.
Keywords: Suhomesnati proizvodi -- Dimljeni pršut -- Pasmina svinja -- Aroma -- Udio masti -- Masne kiseline